Bicameralism, intra-party bargaining, and the formation of party policy positions: Evidence from the German federal system. (May 2016) - Bäck, Hanna; Debus, Marc; Klüver, Heike
How do political parties arrive at their policy positions? We conceptualize position formation in federalist countries as an intra-party bargaining process in which subnational parties compete with each other in an attempt to get their own positions into their national party manifesto. Drawing on theories about inter-party bargaining over ministerial portfolios, we hypothesize that the bargaining success of subnational parties depends on their parliamentary strength. We evaluate our hypotheses based on a comprehensive dataset on policy positions of national and subnational parties in Germany from 1990 until 2009. Our results show that German subnational parties that are powerful in the second parliamentary chamber ( Bundesrat ) are particularly successful in shaping the manifesto of their national party. The findings have important implications for our understanding of intra-party politics and position formation within political parties in Germany more specifically and federalist countries more generally.